Nutritional management of glycogen storage disease type III: a case report and a critical appraisal of the literature - Massimino, Elena; Amoroso, Anna Paola; Lupoli, Roberta; Rossi, Alessandro; Capaldo, Brunella (Frontiers in Nutrition, 2023)
Glycogen storage disease Type III (GSD III) is an autosomal recessive disease due to the deficiency of the debranching enzyme, which has two main consequences: a reduced availability of glucose due to the incomplete degradation of glycogen, and the accumulation of abnormal glycogen in liver and cardiac/skeletal muscle. The role of dietary lipid manipulations in the nutritional management of GSD III is still debated. A literature overview shows that low-carbohydrate (CHO) / high-fat diets may be beneficial in reducing muscle damage. We present a 24-year GSD IIIa patient with severe myopathy and cardiomyopathy in whom a gradual shift from a high-CHO diet (61% total energy intake), low-fat (18%), high-protein (21%) to a low-CHO (32 %) high-fat (45%) / high-protein (23%) diet was performed. CHO was mainly represented by high-fiber, low glycemic index food, and fat consisted prevalently of mono and polyunsaturated fatty acids. After a 2-year follow-up, all biomarkers of muscle and heart damage markedly decreased (by 50-75%), glucose levels remained within the normal range and lipid profile was unchanged. At echocardiography, there was an improvement in geometry and left ventricular function. A low -CHO, high-fat, high-protein diet seems to be safe, sustainable and effective in reducing muscle damage without worsening cardiometabolic profile in GSDIIIa. This dietary approach could be started as early as possible in GSD III displaying skeletal/cardiac muscle disease in order to prevent/minimize organ damage.